2013
DOI: 10.1093/rheumatology/ket293
|View full text |Cite
|
Sign up to set email alerts
|

Gout as a risk factor for myocardial infarction and stroke in England: evidence from record linkage studies

Abstract: Gout was associated with increased risk of stroke as well as MI. These findings should be considered by clinicians and may have implications for preventive management of circulatory disease risks in people with gout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 34 publications
4
73
0
5
Order By: Relevance
“…A different study using the same dataset looking at MI incidence alone found an adjusted HR for MI of 1.23 in the gout group over an 8-year period, with even more pronounced risk in patients without traditional cardiovascular risk factors [21]. An analysis of retrospective analysis of hospital records from the entire UK found that patients who had been admitted to the hospital for gout flares were much more likely to be admitted to the hospital or die from an MI or stroke, with a relative risk (RR) of 1.82 for MI, 1.71 for stroke, with stronger associations seen in younger age groups and in women [22]. However, while this last study has a very impressive scope, it has the significant limitation of being unable to control for a number of potential confounders due to the inability to examine clinical records.…”
Section: Myocardial Infarction and Anginamentioning
confidence: 99%
“…A different study using the same dataset looking at MI incidence alone found an adjusted HR for MI of 1.23 in the gout group over an 8-year period, with even more pronounced risk in patients without traditional cardiovascular risk factors [21]. An analysis of retrospective analysis of hospital records from the entire UK found that patients who had been admitted to the hospital for gout flares were much more likely to be admitted to the hospital or die from an MI or stroke, with a relative risk (RR) of 1.82 for MI, 1.71 for stroke, with stronger associations seen in younger age groups and in women [22]. However, while this last study has a very impressive scope, it has the significant limitation of being unable to control for a number of potential confounders due to the inability to examine clinical records.…”
Section: Myocardial Infarction and Anginamentioning
confidence: 99%
“…The risk of stroke seems to be increased as well in gouty patients. 19 Subclinical indicators of CV involvement, such as the carotid intima-media complex thickness and the presence of atherosclerotic plaques, also seem to be more prevalent in gouty patients than in control non-gouty patients. 20 All these data quite strongly suggest that in gouty patients CV complications of atherosclerosis are heightened, explaining the resulting higher mortality.…”
Section: When To Start Urate Lowering Therapy?mentioning
confidence: 99%
“…Hyperuricemia is an independent risk factor for hypertension, which is one the most common comorbidities of gout (92,93). Hyperuricemia and gout were both found to be associated with increased risk of stroke and myocardial infarction and CV mortality (94)(95)(96). Use of thiazide and loop diuretics has been associated with an increased risk of gout (97).…”
Section: Comorbid Disease Managementmentioning
confidence: 99%